CHARACTERIZATION OF LIPID SUBSTANCES OF ROSE HIP SEEDS AS A POTENTIAL SOURCE OF FUNCTIONAL COMPONENTS: A REVIEW - MANNOZZI, C.; FOLIGNI, R.; SCALISE, A.; MOZZON, M. (Italian Journal of Food Science, 2020)
Functional foods receive the greatest attention for nutritional needs of specific consumers. The rose hip fruit, besides carotenoids and polyphenols, are also good sources of lipid substances (fatty acids, sterols and tocopherols), which can be used as functional foods instead of being discarded as waste. The aim of this review is to present an overview of the lipid characterization of rosehip seeds as affected also by the oil extraction procedure.The rosehip seeds oil is proven to be rich in polyunsaturated fatty acid (PUFA), sterols and tocopherols, which provide specific biological activities (anti-inflammatory, anti-obesity, antioxidant, anti-diabetic activity). In particular, the oil content of rose hip seeds ranges from 5 to 18 % and is composed of unsaturated fatty acids such as linoleic acid (36-55 %) which is the most abundant one, linolenic (17-27 %) and oleic acid (15-22 %) respectively. As for the sterols, its content ranges around 5 g/kg constituting predominantly B-Sitosterol, whereas, the tocopherols amount to around 1 g/kg with Y-tocopherol being the most abundant.